The Influence of the Yanbu'a Method Tahfidz Program on Student Learning Outcomes in Al-Qur'an Hadith Subjects - Yunita Amelia; Asnal Mala; Solchan Ghozali (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The tahfidz yanbu'a method originates from Kudus, Central Java. This method emphasizes how to read and write and memorize the Al-Qur'an effectively and efficiently. Indirectly, the Tahfidz program can make it easier for children to understand religious material, including Al-Qur'an Hadith subjects, where there is a lot of material related to the Al-Qur'an, starting from reading, writing and memorizing. This research aims to determine the effectiveness of the yanbu'a method tahfidz program on student learning outcomes in Al Qur'an Hadith subjects at MI Banu Hasyim. The approach to this research is quantitative research and experimental research. The data collected in this research will be analyzed using the linear regression method and T test hypothesis. The results of this research show that the average student learning outcomes provide very good results with a range of 90-100. 20 students or 50% distribution frequency, which means it can increase students' understanding of the material in accordance with basic competencies and achieve Minimum Completeness Criteria (KKM). The results of hypothesis testing (T Test) show that the tahfidz program variable yanbu'a method (X) has a calculated t value of 6,800 > t table value of 2,290 and a significant value = 0.001 < 0.05, so it states that Ho is rejected and H1 is accepted. This means that there is a significant influence between the yanbu'a method tahfidz program on student learning outcomes in the Al-Qur'an Hadith subject.